Does financial information presentation format matter? Evidence from Chinese firms’ reporting of research and development expense - Mohanram, Partha; Sun, Wei; Xin, Baohua; Zhu, Jigao (Review of Accounting Studies, 2025)
This paper investigates the effects of a regulatory change in China of the presentation format for research and development (R&D) expense, which mandates public firms to explicitly present R&D expense on their income statements. We predict that this regulation will impact nonstate-owned enterprises (non-SOEs), which care about stock market valuation, more than state-owned enterprises (SOEs). We find that non-SOEs report significantly higher R&D expense post regulation. Furthermore, the R&D increase strengthens for firms facing higher peer pressure to pursue R&D and high-tech firms and weakens for firms with higher institutional investment. The positive valuation implication of R&D diminishes post regulation, suggesting that investors discount the increase in R&D expense. An additional analysis shows that firms’ innovation efficiency decreases post regulation.